Improving the Operation of a Distribution Network by Optimal Siting and Sizing of Photovoltaic-Battery Energy Storage Systems - Krstic, Nikola N.; Tasic, Dragan S.; Klimenta, Dardan O.; Milovanovic, Milos J. (Elektronika ir Elektrotechnika, 2024)
This paper proposes an updated two-step approach to improve the operation of a distribution network (DN) through the optimal siting and sizing of one, two, or three systems, each consisting of a photovoltaic (PV) generator and a battery energy storage (BES) unit – the so-called “PV-BES system”. The first step of the approach determines the optimal sites and optimal powers of the PV-BES systems, taking into account the DN load profile and the required improvement in DN operation. Parameters used to describe the quality of the DN operation include the average daily power losses and the voltage profile quality index of the DN. The optimal locations and optimal powers of the PV-BES systems are determined using metaheuristics of the particle swarm optimisation (PSO) and wild horse optimisation (WHO) methods considering various daily load profiles. Based on the optimal powers of the first step and the known daily variation of solar irradiation, the second step provides the individual maximum powers of the PV generators and BES units, as well as the storage capacities of the BES units required for the sizing of the PV-BES systems. The iterative method used for the sizing of the PV-BES systems in the second step of the proposed approach can be regarded as a novelty. Finally, all results were obtained using the IEEE 33-bus test radial DN topology, considering different numbers of PV-BES systems connected to the DN, different efficiencies of the BES units, and different priorities in the criterion function.